Interprofessional educators' competencies, assessment, and training – IPEcat: protocol of a global consensus study. Issue 5 (3rd September 2022) - Paignon, Adeline; Schwärzler, Patricia; Kerry, Matthew; Stamm, David; Bianchi, Monica; Xyrichis, Andreas; Gilbert, John; Cornwall, Jon; Thistlethwaite, Jill; Iwg-Ipecat,; Huber, Marion
ABSTRACT: Contemporary practice in interprofessional education (IPE) has evolved predominantly focusing on the competencies for interprofessional collaboration (IPC) that learners must acquire. Competencies that educators need to successfully deliver IPC have been overlooked. This lack of attention is further confounded by a field replete with inconsistent terminology and standards and no global consensus on the core competencies needed for IPE facilitation. There are no globally accepted tools to assess interprofessional educators' competencies nor are there established training programmes that might be used as the basis for a collective global approach to these issues. The International Working Group for Interprofessional Educators Competencies, Assessment, and Training (IWG_IPEcat) seeks to address this gap using a sequential mixed-method approach, to deliver globally developed, empirically derived tools to foster IPE educator competencies. This article presents the protocol of the research project.